2018
DOI: 10.3389/fmicb.2018.00812
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Electron Acceptor Abundance Drives Selection of Dehalococcoides mccartyi (D. mccartyi) Strains in Dechlorinating Enrichment Cultures and Groundwater Environments

Abstract: Dehalococcoides mccartyi (D. mccartyi) strains differ primarily from one another by the number and identity of the reductive dehalogenase homologous catalytic subunit A (rdhA) genes within their respective genomes. While multiple rdhA genes have been sequenced, the activity of the corresponding proteins has been identified in only a few cases. Examples include the enzymes whose substrates are groundwater contaminants such as trichloroethene (TCE), cis-dichloroethene (cDCE) and vinyl chloride (VC). The associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Hug et al (2013) 19 developed a classication system for reductive dehalogenases where sequences were assigned to Ortholog Groups (OGs) in an attempt to cluster rdhA sequences into groups with similar activity on specic halogenated electron acceptors. 35 Previous studies identied 32 distinct rdhA genes in the KB-1/ TCE-MeOH culture, 38,69,70 with two being identical to genes found previously in D. mccartyi CBDB1. Although 104 RdhA were found in this study, only three new OGs could be described, and the remaining RdhA sequences fell into previously identied groupings (Table S2 †).…”
Section: Reductive Dehalogenase Genes In Dehalococcoides Mccartyi Andsupporting
confidence: 65%
See 1 more Smart Citation
“…Hug et al (2013) 19 developed a classication system for reductive dehalogenases where sequences were assigned to Ortholog Groups (OGs) in an attempt to cluster rdhA sequences into groups with similar activity on specic halogenated electron acceptors. 35 Previous studies identied 32 distinct rdhA genes in the KB-1/ TCE-MeOH culture, 38,69,70 with two being identical to genes found previously in D. mccartyi CBDB1. Although 104 RdhA were found in this study, only three new OGs could be described, and the remaining RdhA sequences fell into previously identied groupings (Table S2 †).…”
Section: Reductive Dehalogenase Genes In Dehalococcoides Mccartyi Andsupporting
confidence: 65%
“…We had previously noted that different electron acceptors enriched for different strains of D. mccartyi. 38 From three cultures, 8 new D. mccartyi genomes were closed, increasing the total number of publicly available D. mccartyi genomes to 24. As well, one new Dehalobacter restrictus genome was closed increasing the number publicly available to 4 (as of December 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Before 33 and after the TCE dechlorination experiment with KB-1/VC, vcrA was the most abundant RDase gene analyzed. The information obtained from the qPCR data therefore suggests that the maintenance on one specific precultivation substrate has a significant influence on the microbial community and the prevalence of RDase genes 35 .…”
Section: Resultsmentioning
confidence: 97%
“…Our results indicate that the type of chlorinated substrate drives the selection of OHRB. Likewise, a recent study showed that a Dehalococcoides population shift was driven by different chlorinated electron acceptors in enrichment cultures containing Dehalococcoides and at a contaminated site (Pérez-de-Mora et al 2018).…”
Section: Discussionmentioning
confidence: 97%